Understanding the Role of Protic Ionic Liquids (PILs) in Reactive Systems: Rational Selection of PILs for the Design of Green Synthesis Strategies for Allylic Amines and β‐Amino Esters. Issue 7 (3rd July 2019) - Bravo, María V.; Fernández, José L.; Adam, Claudia G.; Della Rosa, Claudia D.
Abstract: The reactive behaviour of protic ionic liquids (PILs) has been shown to be governed not only by their chemical structures but also by their global compositions, which include the presence of free acids and bases at equilibrium with ionic pairs. Six PILs composed of primary, secondary, or tertiary alkyl ammonium cations with two couterions, nitrate or acetate, were tested in model reactions with unsaturated substrates. The free species that were naturally present in these liquids were identified by cyclic voltammetry. Only tributylammonium nitrate was found to be mostly composed just of the ionic pair; the other five PILs also contain variable amounts of free acid and amine. In reactive systems, these free species determine the products of the reaction. In particular, allylic amines and β‐amino esters were obtained in good yields (91 and 75 %, respectively) by reaction of conjugated dienes and acrylates in the presence of PILs. By taking into account the actual composition of each PIL, it was possible to direct the reaction path towards a specific product with good yields, to ensure acid catalysis, to avoid polymerization of the substrate, and to promote phase transfer of products. These results establish some useful guidelines for the rational design of new PIL‐based one‐step synthetic strategies. Abstract : Careful selection : Protic ionic liquids (PILs) have active roles when performing as solvents in synthesis. The main product of a reaction strongly depends not only on the PIL's chemical structure and properties but also on its global composition (particularly the presence of free acid). Thus, new one‐step synthesis strategies in the presence of ionic liquids such as ethylammonium nitrate (EAN) and ethylamine (EAA) were proposed for allylic amines and β‐amino esters from conjugated dienes and acrylates, respectively, with very good yields (91–75 %).